Clinical Signs and Pathology Associated With Domoic Acid Toxicosis in Southern Sea Otters (Enhydra lutris nereis) - Miller, Melissa A.; Moriarty, Megan E.; Duignan, Pádraig J.; Zabka, Tanja S.; Dodd, Erin; Batac, Francesca I.; Young, Colleen; Reed, Angelina; Harris, Michael D.; Greenwald, Katherine; Kudela, Raphael M.; Murray, Michael J.; et al. (Frontiers in Marine Science, 2021)
The marine biotoxin domoic acid (DA) is an analog of the neurotransmitter glutamate that exerts potent excitatory activity in the brain, heart, and other tissues. Produced by the diatom Pseudo-nitzschia spp., DA accumulates in marine invertebrates, fish, and sediment. Southern sea otters (Enhydra lutris nereis) feed primarily on invertebrates, including crabs and bivalves, that concentrate and slowly depurate DA. Due to their high prey consumption (25% of body weight/day), sea otters are commonly exposed to DA. A total of 823 necropsied southern sea otters were examined to complete this study; first we assessed 560 subadult, adult, and aged adult southern sea otters sampled from 1998 through 2012 for DA-associated pathology, focusing mainly on the central nervous system (CNS) and cardiovascular system. We applied what was learned to an additional cohort of necropsied sea otters of all demographics (including fetuses, pups, juveniles, and otters examined after 2012: n = 263 additional animals). Key findings derived from our initial efforts were consistently observed in this more demographically diverse cohort. Finally, we assessed the chronicity of DA-associated pathology in the CNS and heart independently for 54 adult and aged adult sea otters. Our goals were to compare the temporal consistency of DA-associated CNS and cardiovascular lesions and determine whether multiple episodes of DA toxicosis could be detected on histopathology. Sea otters with acute, fatal DA toxicosis typically presented with neurological signs and severe, diffuse congestion and multifocal microscopic hemorrhages (microhemorrhages) in the brain, spinal cord, cardiovascular system, and eyes. The congestion and microhemorrhages were associated with detection of high concentrations of DA in postmortem urine or gastrointestinal content and preceded histological detection of cellular necrosis or apoptosis. Cases of chronic DA toxicosis often presented with cardiovascular pathology that was more severe than the CNS pathology; however, the lesions at both sites were relatively quiescent, reflecting previous damage. Sea otters with fatal subacute DA toxicosis exhibited concurrent CNS and cardiovascular pathology that was characterized by progressive lesion expansion and host response to DA-associated tissue damage. Acute, subacute, and chronic cases had the same lesion distribution in the CNS and heart. CNS pathology was common in the hippocampus, olfactory, entorhinal and parahippocampal cortex, periventricular neuropil, and ventricles. The circumventricular organs were identified as important DA targets; microscopic examination of the pituitary gland, area postrema, other circumventricular organs, and both eyes facilitated confirmation of acute DA toxicosis in sea otters. DA-associated histopathology was also common in cardiomyocytes and coronary arterioles, especially in the left ventricular free wall, papillary muscles, cardiac apex, and atrial free walls. Progressive cardiomyocyte loss and arteriosclerosis occurred in the same areas, suggesting a common underlying mechanism. The temporal stage of DA-associated CNS pathology matched the DA-associated cardiac pathology in 87% (n = 47/54) of cases assessed for chronicity, suggesting that the same underlying process (e.g., DA toxicosis) was the cause of these lesions. This temporally matched pattern is also indicative of a single episode of DA toxicosis. The other 13% of examined otters (n = 7/54) exhibited overlapping acute, subacute, or chronic DA pathology in the CNS and heart, suggestive of recurrent DA toxicosis. This is the first rigorous case definition to facilitate diagnosis of DA toxicosis in sea otters. Diagnosing this common but often occult condition is important for improving clinical care and assessing population-level impacts of DA exposure in this federally listed threatened subspecies. Because the most likely source of toxin is through prey consumption, and because humans, sea otters, and other animals consume the same marine foods, our efforts to characterize health effects of DA exposure in southern sea otters can provide strong collateral benefits.